The impact of hybridity on PPP governance and related accountability mechanisms: the case of UK education PPPs. Issue 3 (24th June 2021) - Stafford, Anne; Stapleton, Pamela
Abstract : Purpose: Contemporary organisational landscapes offer opportunities for hybrids to thrive. Public–private partnerships (PPPs) are one thriving hybrid form incorporating the use of resources and/or structures from both public and private sectors. The study examines the impact of such a hybrid structure on governance and accountability mechanisms in a context of institutional complexity. Design/methodology/approach: This study uses an approach that draws on institutional logics and hybridity to examine governance arrangements in the PPP policy created for the delivery of UK schools. Unusually, it employs a comparative case study of how four local governments implemented the policy. It draws on a framework developed by Polzer et al. (2017) to examine the level of engagement between multiple logics and hybrid structures and applies this to the delivery of governance and accountability for public money. Findings: The Polzer et al. framework enables a study of how the nature of hybrids can vary in terms of their governance, ownership and control relations. The findings show how the relationships between levels of engagement of multiple logics and hybrid structures can impact on governance and accountability for public money. Layering and blending combinations led to increased adoption of private sector accountability structures, whilst a hybrid with parallel co-existence of community and market logics delivered a long-term governance structure. Research limitations/implications: The paper examines the operation of hybrids in a complex education PPP environment in only four local governments and therefore cannot provide representative answers across the population as a whole. However, given the considerable variation found across the four examples, the paper shows there can be significant differentiation in how multiple logics engage at different levels and in varying combinations even in the same hybrid setting. The paper focuses on capital investment implementation and its evaluation, so it is a limitation that the operational stage of PPP projects is not studied. Practical implications: The findings have political relevance because the two local government bodies with more robust combinations of multiple logics were more successful in getting funds and delivering schools in their geographical areas. Originality/value: The study extends Polzer et al. 's (2017) research on hybridity by showing that there can be significant differentiation in how multiple logics engage at different levels and in varying combinations even in what was planned to be the same hybrid setting. It shows how in situations of institutional complexity certain combinations of logics lead to differentiation in governance and accountability, creating fragmented focus on the related public accountability structures. This matters because it becomes harder to hold government to account for public spending.